THU0246 Differences (OR Variations) in Physical Functioning in RA by Disease Activity Levels Defined by Das, CDai, and SDAI in Clinical Practice. (10th June 2014) - Alemao, E.; Joo, S.; Kawabata, H.; Al, M.; Allison, P.; Rutten-van Molken, M.; Frits, M.; Iannaccone, C.; Shadick, N.; Weinblatt, M.E.
Abstract : Background: Multiple composite measures of disease activity, such as Disease Activity Score (DAS), Clinical Disease Activity Index (CDAI) and Simplified Disease Activity Index (SDAI), are currently recommended and used to evaluate treatment benefits in RA. However, limited data exist on how key clinical outcomes, such as physical functioning, differ by levels of disease activity in a clinical practice setting. Objectives: Evaluate the association between disease activity levels, as defined by DAS28 (C-reactive protein; CRP), CDAI and SDAI, and physical functioning, as measured by the modified Health Assessment Questionnaire (MHAQ), in clinical practice. Methods: Data from the Brigham and Women's Hospital Rheumatoid Arthritis Sequential Study (BRASS) Registry, established in 2003, were used. 1 The current analysis is based on the first 5 years of patient follow-up in BRASS. Disease activity levels of severe disease activity (SDA), moderate disease activity (MDA), low disease activity (LDA) and remission were based on DAS28 (CRP) (SDA: >5.1; MDA: ≤5.1; LDA: ≤3.2), SDAI (SDA: >26; MDA: ≤26; LDA: ≤11; remission: ≤3.3) and CDAI (SDA: >22; MDA: ≤22; LDA: ≤10; remission: ≤2.8). All independent variables including disease activity (SDAI, CDAI, DAS28-CRP) were measured prior to the outcome (MHAQ). To control for intra-class correlation of the panel data in BRASS, mixed models were used to estimate the fixed and random effects on MHAQ. Variables for the fixed effects include baseline demographics, comorbidities, family history of disease, duration of RA disease, joint replacement, disease activity and seropositivity. Results: A total of 1297 (82.3% female) BRASS patients are included in the current analysis, with a mean (standard deviation [SD]) age of 56.6 (14.1) years and a mean (SD) duration of symptoms of 15.3 (13) years. At baseline, 71% of patients were seropositive; 10.3% (n=134) and 7% (n=91) were in remission based on CDAI and SDAI, respectively. The majority (95%) of patients were exposed to DMARDs and 45% of these were exposed to biologic DMARDs at baseline. Based on univariate analyses, patients in remission/LDA (vs patients in MDA/SDA) tended to have lower mean MHAQ scores (Figure). After controlling for covariates in mixed models, patients who were in remission (vs LDA) had significantly lower MHAQ scores during follow-up based on SDAI (–0.047; p=0.010) and CDAI (–0.073; p=0.0003) criteria. There was no significant difference in MHAQ between DAS ≤2.6 and ≤3.2 (–0.022; p=0.173). Patients who attained remission/LDA (vs MDA and SDA) had significantly lower MHAQ scores across all composite measures. Conclusions: There was no difference in physical functioning between DAS28 (CRP) ≤2.6 vs ≤3.2. However, being in remission (vs LDA), as per CDAI and SDAI, provided additional improvement in the physical function of the patient. Attainment of remission/LDA in clinical practice was associated with improvements in physical functioning. References: Iannaccone CK, et al. Arthritis Care Res (Hoboken) 2013;65:1183–9. Disclosure of Interest: : E. Alemao Shareholder of: BMS, Employee of: BMS, S. Joo Shareholder of: BMS, Employee of: BMS, H. Kawabata: None declared, M. Al: None declared, P. Allison: None declared, M. Rutten-van Molken: None declared, M. Frits: None declared, C. Iannaccone: None declared, N. Shadick Grant/research support: ABBVIE, AMGEN, Genentech, M. Weinblatt Grant/research support: BMS, Crescendo Bioscience, UCB, Consultant for: BMS, Crescendo Bioscience, UCB, Abbvie, Roche, Janssen DOI: 10.1136/annrheumdis-2014-eular.1519